Pembuatan Teh Daun Kelor untuk Peningkatan Ekonomi Masyarakat di Kecamatan Ulakan Tapakis, Padang Pariaman - Matlal Fajri Alif; Yulizar Yusuf; Emriadi Emriadi; Deswati Deswati; Mai Efdi; Novesar Jamarun; Syukri Arief; Adlis Santoni; Bustanul Arifin; Suryati Suryati; Yetria Rilda; Safni Safni; Zilfa Zilfa; Olly Norita Tetra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The Moringa plant, a tropical species, exhibits prolific growth and is abundantly present in Indonesia and other tropical regions worldwide. An extended lifespan, continuous flowering, and a high tolerance for elevated temperatures characterize it. Utilizing its components, including leaves, bark, seeds, and roots, this multifaceted plant is renowned for its therapeutic properties. The plant's antioxidants and various nutrients, including vitamins and minerals (iron, magnesium, vitamin B6, vitamin B2, vitamin C, and vitamin A), have led to studies on the plant's potential health benefits. In order to develop the local economy in Ulakan village, Padang Pariaman Regency, Moringa plants were processed by using the plant leaves to manufacture herbal tea, which can then be sold. This community service program was significant given the widespread presence and ease of cultivation of Moringa plants within the local region. The program involved the planning and selection of the activity site, the implementation of training sessions, and the assessment of the program's outcomes. The result of this community engagement initiative was the demonstrated interest of many participants in producing Moringa leaf tea.